From metabolic reprogramming to epigenetic modification: association network and targeted treatment strategy between histone lactylation and tumor progression - Li, Yi; Feng, Lu; Shen, Qian; Jiang, Xiaochen; Liu, Fudong; Zhang, Chuanlong; Qi, Runzhi; Pang, Bo (Frontiers in Immunology, 2025)
Metabolic reprogramming and epigenetic modification have been widely observed in cancer research. Based on accumulating experimental evidence in recent years, beginning with metabolic reprogramming driven by carcinogenic signals, the accumulation of key metabolites, represented by lactate, continuously affects cellular plasticity and alters the epigenetic landscape. As a new post-translational modification of histone, histone lactylation not only changes the nucleosome structure, but also regulates chromatin dynamics and gene expression, which is closely related to the poor prognosis of tumors, contributing to immune escape, immune monitoring and angiogenic events in tumor progression. Before the discovery of histone lactylation in 2019, there was a lack of systematic understanding of the lactate regulation of tumor metabolism, immune effects and microenvironmental homeostasis. From metabolic changes to stable gene expression, histone lactylation has become an important entry point in tumor research, connecting the relationship network of metabolic reprogramming, Tumor microenvironment (TME) and epigenetic modification. It represents an important conceptual link between metabolism and epigenetics, and emerging evidence suggests it may be a promising area for understanding tumor progression and developing targeted therapies. In this review, we focus on how tumor cell metabolic reprogramming reshapes the epigenetic landscape into histone lactylation. Besides, we discussed the plasticity of tumor metabolism regulated by histone lactylation in reverse, involving TME biological processes such as immunity and metabolism. Finally, we reviewed the new molecular targets and targeted therapeutic strategies of histone lactylation for cancer treatment. Elucidating these problems will provide theoretical basis for further research and clinical application in this field in the future.